Primary Care Follow-up After Emergency Department Visits for Routine Complaints: What Primary Care Physicians Prefer and What Emergency Department Physicians Currently Recommend. Issue 6 (June 2016) - Chen, Jessica; Singer, Eric
Abstract : Objectives: Given that the vast majority of pediatric patients that present to the emergency department (ED) are discharged home after their visit, one issue for study is the appropriate recommendations for follow-up after the ED visit. Numerous PubMed searches using various keywords revealed a gap in the literature regarding the desires of primary care physicians (PCPs) concerning follow-up after ED visits. This study was conducted to determine how pediatric emergency medicine (PEM) physicians' recommendations for follow-up align with the desires of (PCPs) for follow-up after ED visits. Methods: An electronic survey was distributed to pediatric emergency physicians at one community-based academic institution regarding current recommendations for follow-up with PCPs for 12 common diagnoses seen in the ED. A similar survey was sent to pediatricians in the same community inquiring about their desires for follow-up after their patients are seen in the ED for the same diagnoses. Results: Completion rates for the survey were 40/40 (100%) for PEM physicians and 78/145 (54%) for pediatricians. In 11/12 of the diagnoses included, PEM physicians recommended a statistically significant ( P < 0.05) closer follow-up than desired by the PCPs. Conclusions: Recommendations for follow-up made by PEM physicians and desired by PCPs vary significantly. Overall, PEM physicians recommend closer follow-up than desired by PCPs for low acuity complaints. Closing of this gap may allow for a better allocation of resources and consistency of care.